New subgradient extragradient algorithm for solving variational inequalities in Hadamard manifold - Oyewole, O.K. (Optimization, 2024)
This paper introduces a schematic approximation method for a solution to a variational inequality problem in the framework of Hadamard manifold. The method is a combination of the subgradient extragradient technique and Popov extragradient method. Using this method, some convergence algorithms were proved when the cost operators are pseudomonotone and strongly pseudomonotone, respectively. In the construction of this method, the dependence on Lipschitz constants of the operators is dispensed with by the use of a monotone decreasing step size. We give an application of our main result to the constrained convex minimization problem. Finally, we report some numerical examples to illustrate the efficiency and applicability of the method.